Organ manifestations and long-term outcome of Fabry disease in patients with the GLA haplotype D313Y. Issue 4 (8th April 2016) - Oder, Daniel; Üçeyler, Nurcan; Liu, Dan; Hu, Kai; Petritsch, Bernhard; Sommer, Claudia; Ertl, Georg; Wanner, Christoph; Nordbeck, Peter
Abstract : Objectives: The severity of Fabry disease is dependent on the type of mutation in the α-galactosidase A (AgalA) encoding gene (GLA). This study focused on the impact of the GLA haplotype D313Y on long-term organ involvement and function. Setting and participants: In this monocentric study, all participants presenting with the D313Y haplotype between 2001 and 2015 were comprehensively clinically investigated at baseline and during a 4-year follow-up if available. Five females and one male were included. Primary and secondary outcome measures: Cardiac, nephrological, neurological, laboratory and quality of life data. Results: AgalA enzyme activity in leucocytes (0.3±0.9 nmol/min/mg protein (mean±SD)) and serum lyso-Gb3 (0.6±0.3 ng/mL at baseline) were in normal range in all patients. Cardiac morphology and function were normal (left-ventricular (LV) ejection fraction 66±8%; interventricular septum 7.7±1.4 mm; LV posterior wall 7.5±1.4 mm; normalised LV mass in MRI 52±9 g/m 2 ; LV global longitudinal strain −21.6±1.9%) and there were no signs of myocardial fibrosis in cardiac MRI. Cardiospecific biomarkers were also in normal range. Renal function was not impaired (estimated glomerular filtration rate MDRD 103±15 mL/min; serum-creatinine 0.75±0.07 mg/dL; cystatin-c 0.71±0.12 mg/L). One female patient (also carrying a Factor V Leiden mutation) had a transitory ischaemic attack. One patient showed white matter lesions in brain MRI, but none had Fabry-associated pain attacks, pain crises, evoked pain or permanent pain. Health-related quality of life analysis revealed a reduction in individual well-being. At long-term follow-up after 4 years, no significant change was seen in any parameter. Conclusions: The results of the current study suggest that the D313Y genotype does not lead to severe organ manifestations as seen in genotypes known to be causal for classical FD.